Could Eggs Help Increase Dietary Protein Intake in Older Adults? – Exploring Reasons for the Consumption and Non-Consumption of Eggs in People over 55 years old. Issue 3 (2nd October 2018) - van den Heuvel, Emmy; Murphy, Jane L.; Appleton, Katherine M.
Abstract: Compared to other protein-rich foods, eggs are of soft texture, easy to cook, and low cost, and may be useful in increasing protein intakes in older adults. Focus groups and interviews were used to explore all reasons for consuming and not consuming eggs in older adults. Forty-two individuals (20 males, 22 females, aged 56–96 years) took part in one of eight focus groups or two individual interviews. Thematic analyses revealed 69 different reasons for eating or not eating eggs in this population. Reasons were related to: hedonics, properties of the food, preparation style, convenience, physical environment, variety, physical health/abilities, nutrition and health knowledge, food safety, social environment, morality, emotion, and habit. Some of these reasons are likely to be specific to egg consumption in older adults, e.g. properties of the food and convenience combined with physical health/abilities. Some reasons are also likely to be more relevant to older than younger individuals, e.g. medical factors. Investigation of the reasons most related to intake on a population-wide scale would aid the development of interventions.